2019
DOI: 10.1038/s41586-019-1622-4
|View full text |Cite
|
Sign up to set email alerts
|

Windborne long-distance migration of malaria mosquitoes in the Sahel

Abstract: Over the past two decades, control efforts have halved malaria cases globally, yet burdens remain high in much of Africa and elimination has not been achieved even where extreme reductions have occurred over many years, such as in South Africa 1,2 . Studies seeking to understand the paradoxical persistence of malaria in areas where surface water is absent for 3-8 months of the year, suggested that certain Anopheles mosquitoes employ long-distance migration 3 . Here, we confirmed this hypothesis by aerial sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
232
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(253 citation statements)
references
References 64 publications
16
232
2
3
Order By: Relevance
“…Wind dispersal. A recent paper showed that wind dispersal of mosquitoes is possible (Huestis et al, 2019). In this study a maximum wind dispersal of 295 km was observed.…”
Section: Import Pathwayssupporting
confidence: 56%
See 2 more Smart Citations
“…Wind dispersal. A recent paper showed that wind dispersal of mosquitoes is possible (Huestis et al, 2019). In this study a maximum wind dispersal of 295 km was observed.…”
Section: Import Pathwayssupporting
confidence: 56%
“…Most of the outbreaks reported to the OIE between 2006-2019 were located at a distance of more than 30 km from a large airport or port, which is beyond the active flight range of the RVF mosquito vectors (Figure 2, Figure 3, Appendix A). For the modelling of import through flights or ports we assumed that a mosquito can potentially be present at the premises of an airport or port introduced by wind from an outbreak located at a maximum distance of 295 km (Huestis et al, 2019) from the airport or port. The present document has been produced and adopted by the bodies identified above as author(s).…”
Section: Assessment Of the Rvf Outbreaks Reported Between 2006-2019 Tmentioning
confidence: 99%
See 1 more Smart Citation
“…coluzzii and An. gambiae s.s., as well as several secondary malaria vectors regularly engage in seasonal flights 40-290 m above ground (Huestis et al 2019). Because of the large number of migrants, most of which were gravid females, and the large distances they were able to cover, the likely epidemiological significance of such movements was inescapable.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent aerial sampling data (Huestis et al 2019) has led us to modify the latter prediction, to suggest the presence of migrants across the three species. The data from the aerial sampling study (Huestis et al 2019) also led us to modify our initial prediction reflecting the high frequency of gravid females in altitude. Finally, we investigated whether putative migrants (based on our flight mill data) exhibit different wing morphology.…”
Section: Introductionmentioning
confidence: 99%